Peculiarities of Professional Training of Civil Defence Specialists in Ukraine Under a Martial Law - Popovych , Vasyl; Menshykova, Olga (Roczniki Nauk Społecznych, 2024)
The State Emergency Service of Ukraine is a central executive body directed and coordinated by the Cabinet of Ministers of Ukraine through the Minister of Internal Affairs and implementing the state policy in the field of civil defence, protection of the people and territories from emergencies and prevention of their occurrence, elimination of the consequences of emergencies, rescue, firefighting, fire, and industrial safety, activities of emergency services, and hydrometeorological activities. This institution has two higher education schools offering BA training for civil defence bodies and units. At the same time, Russia’s invasion of Ukraine has led to a number of changes in educational training programs for civil defence specialists. Understanding the current threats and recognizing the role of civil defence requires revision of the standards of all specialties, in particular in terms of awareness and preparedness for emergency situations, as well as separation of a set of knowledge, competencies and skills into a separate specialty “civil defence”.